Cardamonin Reduces Acetaminophen-Induced Acute Liver Injury in Mice via Activating Autophagy and NFE2L2 Signaling - Xu, Qiushi; Fan, Yunhui; Loor, Juan J.; Liang, Yusheng; Sun, Xudong; Jia, Hongdou; Zhao, Chenxu; Xu, Chuang (Frontiers in Pharmacology, 2020)
Cardamonin (CD), a naturally occurring chalcone derived from the Alpinia species, has been shown to exert antioxidant and anti-inflammatory activity, but its role in the prevention of acetaminophen (APAP)-induced hepatotoxicity remains elusive. The objective of this study was to determine the protective effects of CD against APAP-induced acute liver injury (ALI) and the underlying mechanisms. Wild-type (WT) or transcription factor nuclear factor erythroid 2-related factor 2 (NFE2L2)-deficient mice were treated with CD (50 mg/kg or 100 mg/kg, i.p.) or vehicle for 24 h. Subsequently, these mice were challenged with APAP (400 mg/kg, i.p.) for 6 h. Liver and blood samples were collected to evaluate liver injury and protein abundance. Treatment with CD significantly reduced APAP-induced hepatotoxicity. Furthermore, CD effectively reduced APAP-induced inflammation by inhibiting high mobility group box 1 (HMGB1)-Toll-like receptor 4 (TLR4)-NOD-like receptor protein 3 (NLRP3) signaling. In addition, CD induced activation of sequestosome 1 (p62) and NFE2L2 signaling and facilitated autophagy. By applying autophagy inhibitor 3-Methyladenine (3-MA; 20 mg/kg, i.p.), further mechanistic exploration revealed that NFE2L2 deficiency promoted autophagic activity induced by CD treatment, which was conducive to the hepatoprotective effect of CD against APAP-induced hepatoxicity in NFE2L2-/- mice. Overall, data suggest that CD has hepatoprotective effect against APAP-induced ALI, which might be contribute to the activation of NFE2L2 and autophagy.